Agaricus bisporus residue-derived Fe/N co-doped carbon materials as an efficient electrocatalyst for oxygen reduction reaction. (11th October 2021) - Chen, Guanyi; Li, Kai; Wu, Zhaoting; Lin, Fawei; Shen, Chenbo; Yan, Beibei
Abstract: Biomass-derived multielement-co-doped carbon materials with ultrahigh active-sites density and unique physicochemical properties hold great promise for oxygen reduction reaction (ORR) in fuel cells and metal-air batteries. Agaricus bisporus residue as a type of biomass waste is produced after microbial growth on biomass substrates, contributing to its natural multidimensional framework and nutrient elements residual. Based on this advantage, this paper further combined with (NH4 )3 PO4 and FeCl3 ·6H2 O to provide N, P, and Fe. Finally, the Fe/N co-doped carbon catalyst with hierarchical porous structure (SN-Fe-ZA) was fabricated by a facile hydrothermal-pyrolysis synthesis route. The characteristic of SN-Fe-ZA exhibited an obvious honeycomb porous structure, high nitrogen doping content of 2.36 at%, and its specific surface area was up to 1646.4 m 2 ·g −1 with abundant micro-/mesoporous. Electrochemical measurements further indicated that SN-Fe-ZA possessed a distinct ORR electrocatalytic activity in alkaline solution. Compared with the electrochemical parameters of commercial Pt/C electrocatalyst, SN-Fe-ZA had the equivalent onset potential (0.968 V) and half-wave potential (0.820 V). Besides, it showed a more excellent electrochemical stability and stronger methanol-tolerant. This research proposed a promising approach to prepare hierarchical porous and multielement-co-doped catalyst from renewable biomass waste as effective cathode electrocatalytic materials for alkaline fuel cells. Graphical abstract: Image 1 Highlights: Agaricus bisporus residue with natural pores is firstly used for ORR electrocatalyst. N and P are effectively doped in a facile manner via (NH4 )3 PO4 introduction. Fe and N are co-doped and Fe−N structures improve the electrocatalyst properties. SN-Fe-ZA shows excellent long-term stability and enhanced methanol tolerance.